2016
DOI: 10.1002/jor.23362
|View full text |Cite
|
Sign up to set email alerts
|

Sacral bone mineral density (BMD) assessment using opportunistic CT scans

Abstract: This study seeks to establish a method for opportunistic evaluation of sacral bone mineral density. This is a retrospective review of 109 scans from 109 patients who had renal-protocol computed tomography (CT) scans performed for any indication during a 3-month period at a single academic institution in 2014. In the collected CT scans, sacral CT-attenuation in multiple regions of interest (ROI) was compared to the L1 CT-attenuation, an internal reference standard, to determine if a correlation existed. The sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…A prospective trial found that the creation of a small cavity in the vertebral body during vertebraplasty reduced the rate of cement leakage . Attenuation of signal on computed tomography scans in sacral regions strongly correlated with lumbar attenuation values, suggesting opportunistic computed tomography scans can be used to assess sacral bone mineral density . When evaluating bone‐implant interfaces, pedicle screw behaviour was better represented with a cadaveric compectomy model than pure pull‐out testing …”
Section: Surgical Repair Scoliosis and Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective trial found that the creation of a small cavity in the vertebral body during vertebraplasty reduced the rate of cement leakage . Attenuation of signal on computed tomography scans in sacral regions strongly correlated with lumbar attenuation values, suggesting opportunistic computed tomography scans can be used to assess sacral bone mineral density . When evaluating bone‐implant interfaces, pedicle screw behaviour was better represented with a cadaveric compectomy model than pure pull‐out testing …”
Section: Surgical Repair Scoliosis and Infectionmentioning
confidence: 99%
“…20 Attenuation of signal on computed tomography scans in sacral regions strongly correlated with lumbar attenuation values, suggesting opportunistic computed tomography scans can be used to assess sacral bone mineral density. 21 When evaluating bone-implant interfaces, pedicle screw behaviour was better represented with a cadaveric compectomy model than pure pull-out testing. 22 Retrospective correlation analyses between thoracic volume modelling from planar x-rays and pulmonary function tests found that scoliosis correction increased thoracic volume and improved total lung capacities in cases where pre-operative lung capacity was severely restrictive.…”
Section: Surgical Repair Scoliosis and Infectionmentioning
confidence: 99%
“…Although the obtained CT image also depends on the absorption of X‐radiation, in contrast to DEXA a 3D replication of the scanned object is produced using a standardized linear attenuation coefficient scale, where air is defined as −1,000 and water as 0, expressed in HU. Also, in human medicine, the use of CT scans obtained for other indications (e.g., CT colonography) to determine bone density is of high interest in current research . All these studies have in common the fact that the HU of a defined 2D region of interest (ROI) is measured in a single or in multiple slice(s).…”
mentioning
confidence: 99%
“…Measuring bone density with computed tomography instead of using dual-energy X-ray absorptiometry (DEXA) has become a focus of interest in the last few years in human and veterinary medicine. [1][2][3][4][5][6][7][8][9][10][11][12][13] However, according to the World Health Organization, the gold standard for quantitative measurements of bone density is dual-energy X-ray absorptiometry (DEXA). 14,15 Both modalities (DEXA and CT) are based on X-radiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation